2016
DOI: 10.1108/jkm-07-2015-0271
|View full text |Cite
|
Sign up to set email alerts
|

Emergent approach to knowledge management by small companies: multiple case-study research

Abstract: Purpose – The purpose of this paper is to investigate the knowledge management (KM) approach followed by small companies. In particular, after introducing the notion of emergent approach, the paper aims to examine if that notion is useful to properly describe the way small businesses approach their KM activities.\ud Design/methodology/approach – The study is based on the results of a qualitative survey involving 12 owners and managers of small companies belonging to the knowledge-intensive business services (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 53 publications
(71 reference statements)
2
50
0
Order By: Relevance
“…Selection of the organization for research was guided by the following premises. First of all, the organization should be large, since large organizations usually have richer experience in knowledge management than small and medium enterprises (Hutchinson and Quintas, 2008;Durst and Runar, 2012;Zieba et al, 2016). In the European Union, large enterprises are those that employ at least 250 employees.…”
Section: Research Methods 31 Data Collectionmentioning
confidence: 99%
“…Selection of the organization for research was guided by the following premises. First of all, the organization should be large, since large organizations usually have richer experience in knowledge management than small and medium enterprises (Hutchinson and Quintas, 2008;Durst and Runar, 2012;Zieba et al, 2016). In the European Union, large enterprises are those that employ at least 250 employees.…”
Section: Research Methods 31 Data Collectionmentioning
confidence: 99%
“…The first pillar of an information flow is a survey of consumer data. Such activity is carried out under the management of commercial manager through feedback received from employees of the area, also including the sales results via ERP system considered not to be fully integrated into the PDP, by the lack of that manager's concern to store and record such information (see Table 2), which corroborates the statement by [25], that the Knowledge Management (KM) in small and medium-sized companies is guided by a lack of planning and informality.…”
Section: Final Considerations and Conclusionmentioning
confidence: 53%
“…Even though there is abundant literature for the implementation available and knowledge management methods and tools are widespread in industry (Zieba et al, 2016), it can be observed that there is still inefficient reuse of available knowledge in engineering design of many organizations. Carro Saavedra & Lindemann (2017) conclude that the reasons for the insufficient knowledge reuse may be various and often unclear.…”
Section: Research Gap and Research Questionmentioning
confidence: 99%